2015
DOI: 10.1007/s10683-014-9427-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual characteristics and behavior in repeated games: an experimental study

Abstract: Using a laboratory experiment, we investigate whether a variety of behaviors in repeated games are related to an array of individual characteristics that are popular in economics: risk attitude, time preference, trust, trustworthiness, altruism, strategic skills in one-shot matrix games, compliance with first-order stochastic dominance, ability to plan ahead, and gender. We do find some systematic relationships. A subject's patience, gender, altruism, and compliance with first-order stochastic dominance have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…As expected, when the costs and benefits of cooperation are realized at the same time, we find no signifi- cant correlation between an individual's degree of impatience and her contribution behavior, neither in NowNow (Spearman's rank correlation: ρ = 0.04, p = 0.746) nor in LaterLater (ρ = −0.11, p = 0.400). This indicates that there is no direct link between cooperativeness and (im)patience per se, which is in line with previous evidence (Fehr and Leibbrandt, 2011;Davis et al, 2016). Time preferences matter, however, in our two asymmetric treatments.…”
Section: The Effects Of Delayed Costs and Benefits On Cooperationsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, when the costs and benefits of cooperation are realized at the same time, we find no signifi- cant correlation between an individual's degree of impatience and her contribution behavior, neither in NowNow (Spearman's rank correlation: ρ = 0.04, p = 0.746) nor in LaterLater (ρ = −0.11, p = 0.400). This indicates that there is no direct link between cooperativeness and (im)patience per se, which is in line with previous evidence (Fehr and Leibbrandt, 2011;Davis et al, 2016). Time preferences matter, however, in our two asymmetric treatments.…”
Section: The Effects Of Delayed Costs and Benefits On Cooperationsupporting
confidence: 92%
“…Apart from the Prisoner's Dilemma game, they further study the effects of delayed payments on Stag-Hunt game choices, as well as bidding behavior in a first and second price auction. Furthermore, Deck and Jahedi (2015b) study behavior in an intertemporal contest game, but find little evidence for any time discounting.4 Two further related papers areFehr and Leibbrandt (2011) andDavis et al (2016). Both studies separately measure individuals' time preferences and cooperation behavior in a static social dilemma game without any delayed payments.…”
mentioning
confidence: 99%
“…does not find a robust relationship between survey responses to question regarding risk attitudes and cooperation. Similarly, Proto et al [2014] and Davis et al [2014] do not find a relationship between risk aversion and cooperation. It is not clear why these three papers found that risk aversion does not correlate with cooperation while Sabater-Grande and Georgantzis [2002] finds that it does.…”
Section: Motives On Cooperationmentioning
confidence: 92%
“…The literature has also not found a robust relationship between gender and cooperation in infinitely repeated games. While some papers find that women tend to cooperate less in some treatments, other papers do not find such a relationship (see Murnighan and Roth [1983], , Sherstyuk et al [2013], Davis et al [2014] and Proto et al [2014]).…”
Section: Motives On Cooperationmentioning
confidence: 99%
“…While I am of course well aware of the bundle of differences in both biology and socialization that distinguish males and females, I was skeptical that these differences could meaningfully affect the way people played simple games. My conversion came fairly recently in a project regarding behavior in indefinitely repeated prisoner dilemma games (Davis, Ivanov, and Korenok ). It is well known that in such games subjects exhibit considerable heterogeneity in their propensities to cooperate and we were interested in identifying individual characteristics that affected cooperative propensities.…”
Section: Five Lessons From Laboratory Economicsmentioning
confidence: 99%